The implementation of nurse initiated and managed antiretroviral therapy in the City of Johannesburg clinics: perceived facilitators and barriers - Mophosho, Zanele (My University, 2015)
Introduction: Antiretroviral therapy (ART) is a lifesaving clinical intervention for people living with HIV (PLHIV). An important barrier to accessing therapy is the shortage of the health workforce particularly doctors. In order to mitigate the shortage, a nurse driven ART delivery approach known as Nurse Initiated and Managed Antiretroviral Therapy (NIMART) has been implemented in the public sector in South Africa and in other countries. NIMART enables professional nurses to initiate HIV positive persons on ART and manage their care at primary health care clinics. This study sought to explore and describe perceptions of operational managers, facility managers and professional nurses on the facilitators and barriers to the implementation of NIMART in the City of Joburg (CoJ) clinics. Methodology: This was an exploratory descriptive qualitative study which used in-depth interviews with a variety of respondents in order to gain insights into their perceptions of the implementation of NIMART in the CoJ clinics. In total, 26 respondents, comprising of operational managers, facility managers and professional nurses participated in the study. Thematic content analysis was used to analyse data drawing from the Donabedian structure-process-outcome framework. Results: The respondents identified the adequacy of NIMART training and mentoring; the availability and use of NIMART guidelines and the integration of NIMART into Primary Health Care (PHC) services as structural facilitative factors for NIMART implementation. The shortage of the health workforce, shortage of antiretrovirals (ARVs), poor referral feedback, food insecurity and the mobility of patients were identified as key structural and process barriers to the implementation of NIMART. Respondents perceived the improvement in quality of life of NIMART patients and the clinics’ ability to retain patients in care as indicative of the success of iii NIMART implementation. Finally, respondent’s suggestions for improving NIMART implementation in CoJ clinics focussed on improving shortage of the health workforce, improving the availability of ARV drugs and providing opportunities for continuing education for professional nurses. Discussion, conclusion and recommendations: In order to mitigate the barriers identified in this study, recommendations were that the City of Joburg should utilize lower level health care cadres such as nursing assistants and lay counsellors to reduce the professional nurses’ workload and thus improve access to treatment. In addition, the City of Joburg should revise the antiretroviral drug allocations to clinics and revise delivery schedules to ensure that clinics do not run out of ARV drugs. The referral feedback process should be strengthened through the referring clinic and the referral hospital jointly developing referral protocols that should be used by both institutions. Finally, the City of Joburg should consider conducting consultative discussions with professional nurses prior to introduction of new programmes and provide opportunities for regular updates for operational managers, facility managers and professional nurses. Future research could look at the role of PHC qualification in the implementation of NIMART.
Research Report submitted in fulfillment of the requirements for the degree of Master in Public Health (MPH) at the University of the Witwatersrand. April 2015
Keywords: HIV; AIDS; Antiretroviral Therapy, Highly Active